Severe Acute Hemolytic Transfusion Reaction Treated with Ruxolitinib and Plasma Exchange - TOPTAŞ, TAYFUR (KARGER, 2021)
Introduction: Acute hemolytic transfusion reaction is a rare but extremely mortal condition. Even small quantities of ABO-incompatible erythrocytes, as much as 50 mL, can lead to fatality. Since there is no successful standard therapy, preventive measures are very important. In this case report, we presented a 29-year-old woman who was transfused with 2 units of AB Rh-positive instead of 0 Rh-positive red blood cells following a cesarean section. As far as we know, this is the first patient in the literature for whom ruxolitinib was used as a part of therapy. Case Report: The patient was referred to our center 22 h after the ABO-mismatched transfusion. On admission, she had severe hemolysis, acute renal failure, and disseminated intravascular coagulation. Massive plasma exchange, hemodialysis, and pulse steroid therapy were commenced. The patient was refractory to first-line therapies. She was intubated on day 2 due to hypoxia, respiratory failure and changes in consciousness. Ruxolitinib, 2 x 10 mg/day, was started on day 3. The patient's clinical status improved on day 6. Ruxolitinib was withdrawn on day 15, and the patient was discharged without any complications or sequels on day 26. Conclusion: Ruxolitinib may be life-saving in patients with ABO-incompatible transfusion reaction which follows a severe and catastrophic course. (c) 2021 S. Karger AG, Basel
Keywords: Acute hemolytic transfusion reaction; Cytokines; Hemovigilance; Ruxolitinib; CELL; ECULIZUMAB